Histopathology of the Plasmodiophora brassicae-Chinese Cabbage Interaction in Hosts Carrying Different Sources of Resistance - Liu, Xitong; Strelkov, Stephen E.; Sun, Rifei; Hwang, Sheau-Fang; Fredua-Agyeman, Rudolph; Li, Fei; Zhang, Shifan; Li, Guoliang; Zhang, Shujiang; Zhang, Hui (Frontiers in Plant Science, 2022)
Clubroot is a serious soil-borne disease of crucifers caused by the obligate parasite Plasmodiophora brassicae. The genetic basis and histopathology of clubroot resistance in two Chinese cabbage (Brassica rapa ssp. pekinensis) inbred lines Bap055 and Bap246, challenged with pathotype 4 of P. brassicae, was evaluated. The Chinese cabbage cultivar ‘Juxin’ served as a susceptible check. The resistance in Bap055 was found to be controlled by the CRa gene, while resistance in Bap246 fit a model of control by a single, unknown recessive gene. Infection of the roots by P. brassicae was examined by inverted microscopy. Despite their resistance, primary and secondary infection were observed to occur in Bap055 and Bap246. Primary infection was detected at 2 days post-inoculation (DPI) in ‘Juxin’, at 4 DPI in Bap055, and at 6 DPI in Bap246. Infection occurred most quickly on ‘Juxin’, with 60% of the root hairs infected at 10 DPI, followed by Bap055 (31% of the root hairs infected at 12 DPI) and Bap246 (20% of the root hairs infected at 14 DPI). Secondary infection of ‘Juxin’ was first observed at 8 DPI, while in Bap055 and Bap246, secondary infection was first observed at 10 DPI. At 14 DPI, the percentage of cortical infection in ‘Juxin’, Bap055 and Bap246 was 93.3%, 20.0% and 11.1%, respectively. Although cortical infection was more widespread in Bap055 than in Bap246, secondary infection in both of these hosts was restricted relative to the susceptible check, and the vascular system remained intact. A large number of binucleate secondary plasmodia were observed in ‘Juxin’ and the vascular system was disrupted at 16 DPI; in Bap055 and Bap246, only a few secondary plasmodia were visible, with no binucleate secondary plasmodia. The defense mechanisms and expression of resistance appears to differ between Chinese cabbage cultivars carrying different sources of resistance.